PAECYLOMYCOTIC ATYPICAL MYOCARDITIS AND ITS TREATMENT IN CHILDREN - A. V. Strelyaeva; E. R. Gasparyan; I. V. Teres; S. S. Zuev; A. T. Sagieva; Kh. N. Shadyeva; N. B. Lazareva; V. M. Sadykov; T. A. Shcheglova (Российский кардиологический журнал, 2011)
In experimental studies using radioactive isotopes in chicken, it has been clearly demonstrated that paecilomycosis diagnostics, based on the detection of mycotic spherules in the blood, is a valid and clinically feasible method. For the first time, paecilomycotic atypical myocarditis (PAM) in children was described. This disease is characterised by anemic and pain syndromes: pain is localized in the arms, and then involves chest, abdominal area, and spinal areas. Modern analgetic agents – movalis, sirdalud, clopheline, and nimesil – are not effective in children with PAM and pain syndrome. The complex treatment included a homeopathic medication Latrodectus mactans C6, as well as diflucan, polyoxydonium, antibiotics, and ferrum lek. The use of Latrodectus mactans C6 was associated with the pain syndrome regression. In 5 animal species, the authors demonstrated that Latrodectus mactans C6 did not have any adverse or toxic effects. The statistical significance of the results was confirmed by p values of ≤0,01–0,05 in the Student test.